2007
DOI: 10.1002/pds.1475
|View full text |Cite
|
Sign up to set email alerts
|

Drug prescribing pattern at the medical outpatient clinic of a tertiary hospital in southwestern Nigeria

Abstract: The low percentage prescription of drugs by their generic name is responsible for the high cost of drugs to patients. Drug use studies are a necessary tool for assessing prescribing patterns in hospitals, recognizing areas for improvement and improving drug prescribing practices in these facilities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
41
5

Year Published

2008
2008
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(54 citation statements)
references
References 12 publications
6
41
5
Order By: Relevance
“…This value correlates with a previous study 9 carried out in Ibadan, which reported the average number of drugs prescribed as 3.2.…”
Section: Discussionsupporting
confidence: 91%
“…This value correlates with a previous study 9 carried out in Ibadan, which reported the average number of drugs prescribed as 3.2.…”
Section: Discussionsupporting
confidence: 91%
“…The low percentage prescription of drugs by their generic name is responsible for the high cost of drugs to patients. Our value is less than that reported in other studies which were 23.6 and 80% drugs were prescribed from essential drugs list (Enwere et al, 2007). Drug use studies are a necessary tool for assessing prescribing problems in hospitals, recognizing areas for improvement and improving drug prescribing practices in these facilities (Bharity et al, 2008).…”
Section: Discussionmentioning
confidence: 59%
“…Recently, there has been a rigorous effort to ensure RUD for which WHO has identified specific drug use indicators that include number and cost of drugs, use of generic names in prescribed drugs and adherence to Essential Drug List (EDL). 15 Gender analysis showed higher number of male patients [187{62%}] than female [113{38%}. As mentioned by previous researcher in Malaysia, the frequency of prescriptions for cardiovascular drugs for men was higher than that for women.…”
Section: Resultsmentioning
confidence: 94%